2022
DOI: 10.18087/cardio.2022.10.n2211
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ferric carboxymaltose treatment on the Tp-e interval and the Tp-e/QT and Tp-e/QTc ratios in heart failure patients with iron deficiency

Abstract: Aim    In heart failure (HF) patients with iron deficiency, cardiac electrical irregularity is a cause of arrhythmias. The aim of our study was to evaluate the effect of ferric carboxymaltose (FCM) treatment on T wave peak to end (Tp-e) interval and the Tp-e / QT and Tp-e / corrected QT (QTc) ratios that reflect the transmural dispersion of repolarization in HF patients with iron deficiency.Material and methods    Forty HF patients with iron deficiency that were treated with FCM were included in our single cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…When SGLT2 inhibitors were added to HF treatment, the ventricular repolarization markers QT, QTc, QTd, Tp-e, and Tpe/QTc were observed to improve positively in the first month 18 . In another study, an improvement in the Tp-e interval and Tp-e / QT and Tp-e / QTc ratios was observed in the third month with intravenous iron treatment in HF patients with iron deficiency 24 . While QTc, Tp-e, and Tp-e/QTc had positive effects, a decrease in NT-proBNP and improvement in symptoms were detected in patients who were switched from ramipril to ARNI, in the first month 23 .…”
Section: Discussionmentioning
confidence: 88%
“…When SGLT2 inhibitors were added to HF treatment, the ventricular repolarization markers QT, QTc, QTd, Tp-e, and Tpe/QTc were observed to improve positively in the first month 18 . In another study, an improvement in the Tp-e interval and Tp-e / QT and Tp-e / QTc ratios was observed in the third month with intravenous iron treatment in HF patients with iron deficiency 24 . While QTc, Tp-e, and Tp-e/QTc had positive effects, a decrease in NT-proBNP and improvement in symptoms were detected in patients who were switched from ramipril to ARNI, in the first month 23 .…”
Section: Discussionmentioning
confidence: 88%